2022
DOI: 10.21037/tp-22-385
|View full text |Cite
|
Sign up to set email alerts
|

Application of IgG antibody titer and subtype in diagnosis and severity assessment of hemolytic disease of the newborn

Abstract: Background:To analyze the effect of different times of pregnancy of type O pregnant women on the occurrence of ABO hemolytic disease of the newborn (ABO-HDN).Methods: From December 2018 to December 2021, 725 pregnant women with O blood group (husbands with non-O blood group) who met the inclusion criteria were collected. There were 116 cases of ABO-HDN, which were summarized and analyzed. The pregnant women were divided into primigravida and non-primigravida groups. The influence of the number of pregnancies o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
1
0
Order By: Relevance
“…28,29 Several studies have shown that higher maternal anti-A or anti-B titers are associated with a greater degree placental transfer and thus a greater degree of hemolysis. [30][31][32] In our patient cohort, type Bþ blood was more likely versus Aþ to require phototherapy (p < 0.001) and for a longer duration (p ¼ 0.001) as well as more likely to receive IVIG (p ¼ 0.003) even though DAT positivity, baseline hemoglobin, APGAR, and bilirubin were all similar. This correlation suggests that neonates with type B blood and subsequently the presence of anti-B antibodies may present a higher risk of ABO HDN.…”
Section: Discussionmentioning
confidence: 76%
“…28,29 Several studies have shown that higher maternal anti-A or anti-B titers are associated with a greater degree placental transfer and thus a greater degree of hemolysis. [30][31][32] In our patient cohort, type Bþ blood was more likely versus Aþ to require phototherapy (p < 0.001) and for a longer duration (p ¼ 0.001) as well as more likely to receive IVIG (p ¼ 0.003) even though DAT positivity, baseline hemoglobin, APGAR, and bilirubin were all similar. This correlation suggests that neonates with type B blood and subsequently the presence of anti-B antibodies may present a higher risk of ABO HDN.…”
Section: Discussionmentioning
confidence: 76%
“…ABO hemolytic disease of the newborn (ABO-HDN) always occurs in the offspring of blood group O mother and newborns born to mothers with blood type A or B [5,6]. The pathogenesis of ABO-HDN resulting from ABO incompatibility remains unclear, but it is widely accepted that maternal antibodies directed against fetal erythrocytes due to ABO incompatibility initiate erythrocyte destruction, leading to the release of excessive bilirubin [7][8][9].…”
Section: Introductionmentioning
confidence: 99%